Fabrication and corrosion resistance properties of super-hydrophobic coatings on iron and steel substrates by creating micro-/nano-structures and modifying rough surfaces. Issue 96 (29th September 2016) - Lv, Dandan; Shao, Hongfei; Gao, Xiang; Lu, Ke; Lu, Haifeng; Ma, Houyi
Abstract : Super-hydrophobic surfaces are usually prepared by manipulating the surface roughness and surface chemistry of various materials. Abstract : Super-hydrophobic surfaces are usually prepared by manipulating the surface roughness and surface chemistry of various materials. Herein, we report two facile, environmentally friendly and inexpensive methods for the fabrication of super-hydrophobic (SH) coatings on cold rolled steel (CRS) and iron substrates using electrodeposition and etching to control surface roughness in combination with the self-assembly technique. By modifying the rough surfaces with stearic acid (SA) and hydrolysed octyltriethoxysilane (OTES), the water contact angles (WCA) of the super-hydrophobic ZnO coatings reaches up to 160° and the WCA of the super-hydrophobic coatings on etched iron is 155°. The mechanisms for the formation of the super-hydrophobic coatings fabricated by SA and OTES self-assembled thin films on rough steel and iron substrates are investigated by means of attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). Electrochemical impedance spectroscopy (EIS) results show that the SH coatings effectively protect the substrate metals from corrosion in 3.5% NaCl solution and increase the inhibition efficiency to approximately 93% and 86%, for the super-hydrophobic ZnO coating and super-hydrophobic silica coating on etched iron, respectively.